PELATIHAN DESAIN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY UNTUK GURU SMP NEGERI 18 TEBO - Winda Trisnawati; Levandra Balti; Gita Dhia Fadhila (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
The training activity was carried out to equip teachers with the knowledge and practical skills in creating interactive learning media based on augmented reality. The training was carried out in several stages, starting from an introduction to the basic concepts of augmented reality, demonstrations of the use of supporting applications, to direct practice in media creation and assistance in designing learning content. This activity took place periodically and was carried out in a participatory manner so that teachers could develop skills gradually. The results of the activity showed that the training had a positive impact on improving teacher competence in utilizing technology as a teaching aid. Teachers were able to produce more interesting and interactive learning media, and demonstrated high motivation in implementing this technology in the classroom. This activity concluded that training on augmented reality-based media is a strategic step in improving the quality of learning and encouraging educational innovation in the school environment.